Basic of image processing and analysis with image-J / Dr. Zolkapli Eshak and Dr. Gurmeet Kaur Surindar Singh - Eshak, Zolkapli; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
On the 15th March 2023 a workshop on "Basic of Image Processing and Analysis using ImageJ" was held at The Gallery, Level 5, FF1 Building, Faculty of Pharmacy, UiTM Puncak Alam. The workshop was attended by 23 participants from various institutions, who were keen to learn about image processing and analysis techniques. The workshop was conducted by Dr. Zolkapli Eshak, an experienced researcher in the field of image analysis. The participants were introduced to the ImageJ software, a popular open access tool used in image analysis. Dr Zolkapli demonstrated how to use ImageJ for image enhancement, which involved adjusting the brightness, contrast, and color balance of an image to enhance its details. The participants also learned how to add a scale bar to their images, an essential element when presenting scientific data.